Evaluasi Program Pemusatan Latihan Cabang Olahraga Senam Kabupaten Pati Persiapan Kejuaraan Provinsi Jawa Tengah - Sulistiyo, Anatri; Rahayu, Setya; Sugiharto, Sugiharto (Journal of Physical Education and Sports, 2017)
Penelitian ini adalah penelitian evaluasi program menggunakan metode penelitian kualitatif, dengan model pendekatan evaluasi program Countenance Model, sumber data penelitian meliputi pengurus PERSANI Pengkab Pati, pelatih senam, dan atlet senam di Kabupaten Pati. Teknik mengumpulkan data menggunakan observasi, wawancara, dokumentasi dan triangulasi data. Analisis datanya; reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian: atecendent dalam program pemusatan latihan senam di Kabupaten Pati tidak bisa berjalan dengan baik. Sarana prasarana tidak baik. Dukungan pemerintah masih minim. Sumber daya manusia sudah baik. Biaya program pemusatan latihan senam masih minim. Transcation pelaksanaan latihan program pemusatan latihan senam di Kabupaten Pati berjalan baik. Penerimaan atlet tidak ada seleksi khusus. Pelatih ditunjuk dari mantan atlet. Penggunaan sarana dan prasarana kurang baik, koordinasi sudah baik. Outcome program pemusatan latihan senam ada peningkatan hasil kemampuan atlet selama latihan dan peningkatan prestasi atlet. Kesejahteraan atlet dan pelatih masih kurang baik.This is a research on program evaluation by way of qualitative method, and program evaluation approach of Countenance Model; sources of data for this research are the District Board of the Indonesian Gymnastics Association (PERSANI) of Pati, all gymnasts and their coaches in Pati District. Techniques used to collect the data are by way of observation, interview, documentation, and data triangulation. Data analysis procedures: data reduction, data presentation, drawing conclusion. Research result demonstrates: The antecedentcondition of the training center program didn’t develop quite well. The means and facilities were poor. Government support was inadequate. Human resources were improved. The training center program was poorly financed. The progress of thetransaction/ processof the training center program was good. There was no specific selection system developed to recruit the athletes. Coaches were former athletes. The means and facilities were poorly used, while the coordination was good. The outcomeof the training center program showed progress in the athletes’ skills during the training and increase in their performance. The athletes and their coaches’ welfare was not favorable.